(untitled) (Historia, 2021)
I met Burridge almost 35 years ago to the day when I began at the University of South Africa (Unisa) at the beginning of August in 1973. I was very dubious about coming to Unisa from Pietermaritzburg. It had a reputation very different to what I had been used to at the University of Natal and I was greatly relieved when on my first day I met Burridge and found in him a kindred spirit. We both shared a very similar vision of what history means and were politically akin.